Causal associations between insulin-like growth factor 1 and vitamin D levels: a two-sample bidirectional Mendelian randomization study - Gou, Zhaoyang; Li, Fan; Qiao, Fengzhen; Maimaititusvn, Gulinuer; Liu, Fang (Frontiers in Nutrition, 2023)
Background: Insulin-like growth factor 1 (IGF-1) plays a vital role in the attainment and maintenance of bone mass throughout life and is closely related to the stature of children. 25-Hydroxyvitamin D (25-OHD) is an intermediate of vitamin D (Vit D) metabolism and a key indicator of Vit D nutritional status. Multiple studies have revealed that IGF-1 levels undergo a non-significant increase after Vit D supplementation. Here, we analyzed the causal and reverse causal relationships between 25-OHD and IGF-1 levels using Mendelian randomization (MR). Methods: Two-sample MR was used to estimate an unconfounded bidirectional causal relationship between the level of IGF-1 and those of Vit D and 25-OHD. Single nucleotide polymorphisms (SNPs) were filtered from genome-wide association studies (GWAS) after a comprehensive search of the Integrative Epidemiology Unit GWAS database. Several MR methods were employed, including inverse-variance weighted (IVW) method, and a sensitivity analysis was undertaken to detect whether pleiotropy or heterogeneity biased the MR results. Results: Genetically predicted IGF-1 was found to have a causal association with Vit D and serum 25-OHD levels, where Vit D and serum 25-OHD levels increased with increasing IGF-1 concentrations (Vit D: IVW β:0.021, 95% CI: 0.005 to 0.036, p＝7.74x10-3; 25-OHD: IVW β: 0.041, 95% CI: 0.026 to 0.057, p=2.50x10-7). A reverse causal effect was also found, indicating Vit D and serum 25-OHD have a positive causal relationship with IGF-1. (Vit D: IVW β:0.182, 95% CI: 0.061 to 0.305, p＝3.25x10-3; 25-OHD: IVW β: 0.057, 95% CI=0.017 to 0.096, p=4.73x10-3). The sensitivity analysis showed that horizontal pleiotropy was unlikely to bias the causality in this study (MR-Egger: Vit D intercept p=5.1x10-5, 25-OHD intercept p=6.4x10-4 in forward analysis; Vit D intercept p=6.6x10-4, 25-OHD intercept p=1.9x10-3 in reverse analysis), and a leave-one-out analysis did not identify evidence of bias in the results. Conclusion: The results of the MR analysis provide evidence that IGF-1 has positive causal and reverse causal relationships with Vit D and serum 25-OHD, respectively, in European populations. Our findings also provide guidance for the prevention and treatment of short stature and other related diseases.